Entrance to the Suhaveshwar Temple Complex - Temples of India Project Team (Jio Institute, 2024)
The Suhaveshwar temple complex is situated to the west of the Menali stream, a little away from the Mahanaleshvar temple complex. The complex is entered through an entrance gateway which is situated to the east of the complex. The superstructure of this entrance gateway has not survived. Only the main entrance opening is flanked by two broad walls. There is minimal ornamentation on this entrance gateway. The front, east-facing walls of the entrance gateway have empty niches.